2023
DOI: 10.1002/cncr.34696
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of access in Hispanic cancer screening disparities

Abstract: Background: Hispanic populations in the United States experience numerous barriers to care access. It is unclear how cancer screening disparities between Hispanic and non-Hispanic White individuals are explained by access to care, including having a usual source of care and health insurance coverage. Methods:A secondary analysis of the 2019 National Health Interview Survey was conducted and included respondents who were sex-and age-eligible for cervical (n = 8316), breast (n = 6025), or colorectal cancer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…An example is tailoring a colon cancer screening to fit a community's cultural and social norms. Hispanic men have high rates of colon cancer and yet the lowest rate of colon cancer screening [22]. The system needed to improve the screening program implementation for this group will look different than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…An example is tailoring a colon cancer screening to fit a community's cultural and social norms. Hispanic men have high rates of colon cancer and yet the lowest rate of colon cancer screening [22]. The system needed to improve the screening program implementation for this group will look different than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Improving cultural sensitivity and health literacy are necessary to increase Hispanic people's access to and use of health services in managing chronic illnesses, promoting healthy lifestyles, preventing obesity, fostering workplace safety, and encouraging the use of screening and preventive services (Spencer et al, 2023; Velasco-Mondragon et al, 2016). For health-care providers, listening and observing are indispensable tools for assessing Hispanic patients, and for building open communication with patients and their families to allow for effective teaching and care (Johnson & Farquharson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural insensitivity by health-care providers poses serious threats to Hispanic patients who may avoid preventive counseling. Hispanic patients are less likely to be screened for cervical and colorectal cancer (Castillo et al, 2021; Spencer et al, 2023), have less follow-up care, and are more likely than Non-Hispanic Whites to receive mental health care through Emergency Departments rather than outpatient services (Velasco-Mondragon et al, 2016). Given the high prevalence of diabetes and obesity within the Hispanic population, it is discouraging to learn that only 20% of Hispanic patients reported that their providers had discussed diet and exercise with them within the previous year (Velasco-Mondragon et al, 2016).…”
Section: Inadequate Cultural Competence Among Providersmentioning
confidence: 99%
“…CRC screening guidelines are strongly supported by ef-fectiveness data, but use of screening in the US is suboptimal (2)(3)(4)(5). In 2022, the percentage of Hispanic adults who reported being up to date with CRC screening was lower (61.7%) than among non-Hispanic White (74.6%) and non-Hispanic Black (75.3%) adults (6). In addition, being male, having a low level of education, living in poverty, lacking health insurance, and using English as a second language have been associated with lower rates of CRC screening (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 97%